Valorization of grape by-products: Insights into sustainable industrial and nutraceutical applications - Mitali Bhutani; Supriya Singh Gaur; Rafeeya Shams; Kshirod Kumar Dash; Ayaz Mukarram Shaikh; Kovács Béla (Future Foods, 2025)
Grapes and their by-products are also considered abundant sources of protein, fatty acids, and a range of phytochemicals, e.g., resveratrol, quercetin, anthocyanins, procyanidins, catechin, kaempferol, etc. Indeed, researchers revealed several therapeutic advantages of grapes and their constituents, including the ability to fight oxidative stress, maintain heart health, lower inflammation, retard aging processes, and provide antimicrobial and blood sugar-lowering effects. Grapes and its derivatives are also being utilized in preparation of widely consumed products like wine, grape juice, raisins, fermented milk, jam etc. Owing to these benefits, its natural preservatives are gaining traction as a sustainable alternative to synthetic chemicals, contributing to cleaner and greener product formulations across industries. However, existing studies rarely emphasise all aspects of grapes and their by-products, especially its potential application in different sectors. This review integrates various new facets of grapes and their byproducts, highlighting their nutritional and phytochemical abundance while elucidating their therapeutic potential and numerous applications. By elucidating these advantages, the importance of grape derivatives and their role in fostering a healthier and more sustainable future can be emphasised. Accordingly, isolating additional bioactive compounds from grape derivatives holds significant potential to boost the economic value of grape cultivation, foster sustainability, and enhance public health through the advancement of novel therapeutic products.